Fenofibrate Inhibits Subretinal Fibrosis Through Suppressing TGF‐β—Smad2/3 signaling and Wnt signaling in Neovascular Age‐Related Macular Degeneration - Chen, Qian; Jiang, Nan; Zhang, Yuhan; Ye, Sihao; Liang, Xu; Wang, Xin; Lin, Xiang; Zong, Rongrong; Chen, Haoyu; Liu, Zuguo (Frontiers in Pharmacology, 2020)
Subretinal fibrosis is a common pathological change that causes vision loss in neovascular age-related macular degeneration (nAMD). Treatment modalities for subretinal fibrosis are limited. In the present study, the effects of fenofibrate, a specific peroxisome proliferator-activated receptor alpha (PPARα) agonist, on subretinal fibrosis of nAMD were tested, and its molecular mechanisms of action were delineated. Collagen deposition and protein expression of fibrotic markers, such as vimentin, collagen-1, alpha-smooth muscle actin (α-SMA) and fibronectin, were increased in very-low-density lipoprotein receptor (VLDLR) knockout mouse, indicating Vldlr-/- mice can be used as a model for subretinal fibrosis. Fenofibrate suppressed subretinal fibrosis of Vldlr-/- mice by reducing collagen deposition and protein expression of fibrotic markers. Two fibrotic pathways, TGF-β/Smad2/3 signaling and Wnt signaling were significantly upregulated, while inhibited by fenofibrate in Vldlr-/- retinas. Moreover, fenofibrate significantly reduced the downstream connective tissue growth factor (CTGF) expression of these two pathways. Müller cell was a major source of CTGF in Vldlr-/- retinas. Fenofibrate was capable of suppressing Müller cell activation and thus reducing the release of CTGF in Vldlr-/- retinas. In cultured Müller cells, fenofibrate reversed TGF-β2 induced-upregulation of Wnt signaling and CTGF expression. These findings suggested that fenofibrate inhibits subretinal fibrosis by suppressing TGF-β/Smad2/3 signaling and Wnt signaling and reducing CTGF expression; and thus fenofibrate could be a potential treatment for nAMD with subretinal fibrosis.